Association between circulating levels of ACE2-Ang-(1–7)-MAS axis and ACE2 gene polymorphisms in hypertensive patients. Issue 24 (June 2016) - Liu, Dan; Chen, Yongyue; Zhang, Ping; Zhong, Jiuchang; Jin, Lijun; Zhang, Caojin; Lin, Shuguang; Wu, Shulin; Yu, Huimin
Abstract : Abstract: The angiotensin-converting enzyme 2-angiotensin-(1–7)-MAS axis (ACE2-Ang-[1–7]-MAS axis) plays an important role in the control of blood pressure. Some previous studies indicated that the genetic variants of ACE2 may have a potential to influence this axis. Therefore, the present study aimed at examining the association of ACE2 polymorphisms with circulating ACE2 and Ang-(1–7) levels in patients with essential hypertension. Hypertensive patients who met the inclusion criteria were enrolled in the present study. Three Tag single-nucleotide polymorphisms (rs2106809, rs4646155, and rs879922) in ACE2 gene were genotyped for all participants. Circulating ACE2 and Ang-(1–7) levels were detected by enzyme-linked immunosorbent assay. There were 96 (53.0%) females and 85 (47.0%) males participating in the present study. The circulating Ang-(1–7) levels were significantly greater in female patients carrying the rs2106809 CC or CT genotype compared with those carrying the TT genotype (1321.9 ± 837.4 or 1077.5 ± 804.4 pg/mL vs 751.9 ± 612.4 pg/mL, respectively; P = 0.029, analysis of variance), whereas the circulating Ang-(1–7) levels were comparable among genotypes in male patients. In addition, there was no significant difference in the circulating ACE2 levels among rs2106809 CC, CT, and TT genotype groups in both female and male patients. The circulating ACE2 and Ang-(1–7) levels were related to neither rs4646155 nor rs879922 in female or male patients. In conclusion, the rs2106809 polymorphism of the ACE2 gene may be a determinant of the circulating Ang-(1–7) level in female patients with hypertension, suggesting a genetic association between circulating Ang-(1–7) levels and ACE2 gene polymorphisms in patients with hypertension.